The influence of the Anaxagorean denial of the génesis in Aristotelian physics - Díaz, María Elena (Revista Archai, 2022)
Physics I, the homogenization of disparate concepts of the first physicists, as part of the construction of his taxonomy of positions on principles. This propaedeutic strategy of the refutation consists in the assembly of a progression and a genealogy of the positions of the physicists from Eleatism. The main objective of this work is to show the specific meaning of the concept of separation in Anaxagoras' physics and the transformations that undergoes under Aristotelian criticism. In line with recent works such as those of Curd (2019) and Marmodoro (2017) that have drawn attention to the specificity of Anaxagoras' physical vocabulary, this research shows that the bases of his denial of genesis and its reworking in terms of separation and mix rest on original theses of his own physics. Both terminologically and conceptually, the notions of Anaxagorean separation and mixing cannot be exported to another physical theory.